The Basic Values of Pi`il ‎Pusenggighi‎ in ‎the Kuntara Rajaniti Jugulmuda ‎Law - Bunyana Sholihin; Maimun Maimun; Agus Hermanto; Hepi Riza Zen (TSAQAFAH, 2022)
This article is the result of a study of the local wisdom values of the Lampung indigenous people (Pi`il Pusenggighi) in the ancient manuscripts of Kuntara Rajaniti and Jugulmuda. More specifically, this article wants to know the basic values of the social philosophy of the Lampung indigenous people are in the ancient text and how the content of Islamic teachings on the husband and wife rules. The research was conducted using a socio-philosophical approach and content analysis theory to answer this question. As a result, there are many Islamic values contained in the ancient manuscripts of Kuntara Rajaniti and Jugulmuda and the basic values of the social philosophy of the indigenous people of Lampung (Pi`il Pusenggighi). Another conclusion is that the basic values of the social philosophy of the Lampung indigenous people are full of Islamic values. Especially in the introduction to describe the Prophet Muhammad. Besides that, it also applies the analogy proposition similar to the Qiyâs proposition in Islam.Keywords: Pi`il Pusengighi, Social Philosophy, Lampung, Ancient manuscripts, Kuntara.